PENGEMBANGAN MEDIA ULAR TANGGA PADA MATA PELAJARAN MATEMATIKA MATERI PECAHAN (ARTACA) TERHADAP HASIL BELAJAR KELAS III SD - Khoirum Nur Fadilah; Ery Rahmawat; Tri Achmad Budi Susilo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Everything that can be used to convey messages or information during the teaching and learning process is called learning media. Teaching mathematics, especially fractions, will be easier if you use learning media. Teachers and educators still use lectures and assignments as learning methods, so students may not understand the fraction material. Thus, researchers must apply the Snakes and Ladders learning media to evaluate students' responses to the media and to identify differences between pre- and post-test results. The author uses research and development (R&D). This research and development uses Sugiyono's development model modified from Borg and Gall. The research was conducted on class III students at Masangan Wetan Elementary School with a total of 33 students. The results of the research show that 88.5% of students understand the fraction material better after using Snakes and Ladders media, thus showing that Snakes and Ladders media is suitable for use. From the results of the questionnaire calculation, media validation obtained a score of 84% (very feasible) and material validation obtained a score of 88.5% (very feasible) and was proven to be able to improve learning outcomes achieved with a satisfaction score of 87.6 (strongly agree), and learning outcomes Students experienced an increase, initially the completion score of the pretest questions obtained a percentage of 73.3% in the good category and the completion score of the posttest obtained a percentage of 87.5% in the very good category. Therefore, it can be concluded that the development of fractional snakes and ladders media (ARTACA) can improve the learning outcomes of grade III elementary school students.